ACTIVITY OF ACID AND ALKALINE PHOSPHATASES IN THE EGGS OF SOME FRESHWATER TELEOSTS - Shaffi, S A; Jafri, A K (Indian Journal of Fisheries, 2011)
Litfle attention has been paid in the past to the localization and measurementof various enzymatic activities of fish egg with a view to understanding itsmetabolic activity. In an earlier communication from this laboratory the activityof two phosphomonoesterases, the acid and alkaline phosphatases, v(?ere describedin the ripe, unspawned eggs of a few species of freshwater fishes (Jafri andKhawaja, 1967a). The studies on the activities of these enzymes were laterextended to the eggs of some more fishes, as a continuatioo of earlier work, andthe results have been described in the present paper. It its-hoped that the presentset of experiments would yield additional information on fish phosphatasesand would be interesting from the standpoint of comparative biochemistry andphysiology.